Pendorong Investasi Asing: Analisis Ekonomi Provinsi Indonesia Tahun 2021 - Rahma, Laila Fitria Nur; Rohmah, Farida (Universitas Halu Oleo, 2023)
The Indonesian economy has undergone complex developments in recent years. Economic progress is the result of various factors such as Regional Gross Domestic Product (RGDP) growth, the value of exported goods, and average worker wages. Indonesia, as a developing country, faces various challenges in promoting sustainable economic growth. This research aims to analyze the influence of average worker wages, RGDP, and the value of provincial goods exports on the realization of Foreign Direct Investment (FDI) in Indonesia in 2021. This study is quantitative, and data were collected from secondary sources, the official website of the Central Statistics Agency (BPS), and the Investment Coordinating Board (BKPM). The applied analytical method involves the use of multiple linear regression with the support of Eviews 12 software. The research findings indicate that average worker wages do not have a significant impact on the realization of FDI in Indonesia in 2021. Conversely, RGDP and the value of exported goods have a positive and significant influence on FDI realization.